A novel rank order LoG filter for interest point detection - Miao, Zhenwei (2013)
This paper proposes a novel non-linear filter, named rank order LoG (ROLG) filter, and a new interest point detector, named ROLG detector. The ROLG filter is a weighted rank order filter. It is used to detect image structures whose significant majority of pixels are brighter (or darker) than the significant majority of pixels in their corresponding surroundings. The ROLG detector is built on this filter. Compared to linear filter based detectors, the proposed rank order filter based detector is more robust to abrupt variations of images. Experiments on the benchmark databases demonstrate that the ROLG detector achieves superior performance compared to four state-of-the-art detectors. Evaluation experiments are also conducted on face recognition. The results further demonstrate that the ROLG detector has better performance compared to other detectors.